Making Black Los Angeles : Class, Gender, and Community, 1850-1917. - Campbell, Marne L. (The University of North Carolina Press, 2016)
Black Los Angeles started small. The first census of the newly formed Los Angeles County in 1850 recorded only 12 Americans of African descent alongside a population of more than 3,500 Anglo Americans. Over the following 70 years, however, the African American founding families of Los Angeles forged a vibrant community within the increasingly segregatedand stratified city. In this book, historian Marne L. Campbell examines the intersections of race, class, and gender to produce a social history of community formation and cultural expression in Los Angeles.